A bibliometric review study of Michael Burawoy - Raj, Aditya; Sinha, Anushka (Frontiers in Sociology, 2024)
This review article utilizes the technique of citation-based bibliometric analysis to provide a comprehensive understanding of the scholarly contributions made by sociologist Michael Burawoy. The most influential academic articles published by Burawoy were retrieved for analyses. Following this, scholars, journals and institutions that he most frequently collaborated with were traced. Further, country-wise analysis of his scholarship was carried out.Lastly, content analyses of retrieved articles identified prominent thematic domains in sociology to which Burawoy contributed, while temporal analyses helped to identify some emerging research hotspots. Findings reveal that historical and cultural context of Burawoy's research mostly remained confined to the U.S.A., however, he significantly contributed towards the foundation of sociology in the Global South and studied the ensuing global power imbalances.Contemporary sociological thought remains indebted to Burawoy for his comparative study of industrial relations in the 21 st century, and recently, his elaboration upon the need for public sociology has taken the discipline in new intellectual directions that appeals to a broader sociological community.